Analysis of the Evaporator Components of the Adsorption Cooling Machine Using 3D Simulation - Anthony Tannady (International Journal of Mechanical Computational and Manufacturing Research, 2021)
Solar Energy is the biggest energy on the earth, solar enegy in Indonesia can be utilized for variety of things. Based on solar radiation data collected from 18 locations in Indonesia, solar radiation for West Indonesia area has reached 4,5 kWh/m2/day with monthly variation about 10%, while East Indonesia area has reached about 5,1 kWh/m2 /day with monthly variation about 9%. Therefore, the solar energy can be utilized as the main source of energy for the adsorption refrigeration cycle cooling machine to produce cooling effect. The simulation object of this research is evaporator, which simulated with Ansys 15.0 and modeled with 3D CAD software. Evaporator is filled with 5 litres of methanol, and 6 liters of chilled water. This simulation simulated 30 minutes of desorption which start from 5.30 p.m to 6.00 p.m GMT+7 actual research time. The lowest chilled water temperature get from this simulation is about 19,79 ℃ at 12665 Pa pressure, and have an error presentage about 7,21% compared with the actual experiment. Theoretical efficiency of the evaporator is about 57,292% and have an error presentage about 5,21% compared with the actual experiment. Coefficient of Preformance from this cycle is 0,039.